Numerical study of surrounding rock heat dissipation and wind temperature prediction in high geotemperature coal face - Hao Wang (Energy Exploration & Exploitation, 2024)
The heat damage in a coal face of a high-temperature mine is a significant mine disaster owing to various heat sources. Understanding the influence of various heat sources on the air temperature distribution in the coal face can help us to determine reasonable working conditions. Therefore, it is necessary to take into account the coupling relationship of multiple heat sources and obtain accurate prediction results. In this paper, the finite volume calculation method is used to establish a numerical model of heat dissipation of surrounding rock considering the difference in thermal and physical properties of coal and rock in the coal face. And then, a high-temperature coal mine in the northeast of China is taken as an example to explore the airflow temperature distribution law of the coal face under the influence of the absolute heat source and the relative heat source via the finite difference method. Furthermore, an orthogonal test was performed to investigate the influence degree of major factors on heat exchange of the coal face through range analysis. This work supplements the existing numerical model and research, and provides a theoretical basis and more accurate practical methods for predicting the thermal environment of coal face, especially in high mining depth mines.